1999
DOI: 10.1002/(sici)1097-0215(19991112)83:4<497::aid-ijc11>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrins and E‐cadherin cooperate with IGF‐I to induce migration of epithelial colonic cells

Abstract: Although the detailed mechanisms of cell migration remain largely unknown, it is now clear that growth factors and cell adhesion molecules are crucial for this process. We have shown that type I insulin-like growth factor (IGF-I) promotes migration of human colonic tumour cells. Since morphological analysis suggested an involvement of adhesion molecules, we have now examined the role of integrins (cell-matrix adhesion molecules) and E-cadherin/catenins complex (cellcell adhesion molecules) in the IGF-I-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…In breast cancer cells, Guvakova and Surmacz (1997) have shown that IGFR1 enhances adherence via Ecadherin complexes. In colon cancer cells, both E- cadherin and integrins may cooperate with IGFR1 to enhance migration (Andre et al, 1999). Several lines of evidence suggest that direct interactions between integrin and IGFR1 signaling pathways exist.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cells, Guvakova and Surmacz (1997) have shown that IGFR1 enhances adherence via Ecadherin complexes. In colon cancer cells, both E- cadherin and integrins may cooperate with IGFR1 to enhance migration (Andre et al, 1999). Several lines of evidence suggest that direct interactions between integrin and IGFR1 signaling pathways exist.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in C10 colorectal cancer cells, IGF-I-stimulated cell spreading, which was accompanied by tyrosine phosphorylation of beta-catenin, dissociation of beta-catenin from E-cad and translocation of beta-catenin from a sub-membrane to a cytoplasmic compartment (Playford et al, 2000). In addition, Andre' et al (1999) demonstrated enhanced tyrosine phosphorylation of beta-catenin upon IGF-I stimulation in an APC-mutated colorectal cancer cell line, HT29. This resulted in down-regulation of E-cad and increased cell motility.…”
Section: Igf-ir Modulates the E-cadherin Complexmentioning
confidence: 99%
“…For example, activation of IGF-IR and subsequent activation of PI3K and mitogen-activated protein kinase pathways induces motility of neuroblastoma cells (Meyer et al, 2001). By affecting integrin relocation and association of the E-cadherin/catenin complex with the cytoskeleton, IGF-I stimulates migration of epithelial colonic cells (Andre et al, 1999) and myeloma cells (Tai et al, 2003). IGF-IR controls lung carcinoma cell motility and invasion by coordinately regulating expression and activation of matrix metalloproteinase-2 (Zhang and Brodt, 2002).…”
Section: Introductionmentioning
confidence: 99%